The Last Dance: Violence Against Child Sex Workers in Indonesia - Rosyadi Khoirul; Edy Purwanto (Pusat Studi Gender, Universitas Kristen Indonesia, 2023)
This research is a qualitative research that looks at how violence occurs to child sex workers in Dolly (before it was closed) Surabaya. This research method uses qualitative research with a case study approach. The results showed that child sex workers in Dolly Surabaya experienced physical, economic, or psychological violence from pimps and customers. This happens because of their dependence on pimps or moms economically. Child sex workers cannot put up any resistance.